Alterations in T lymphocytes and T-lymphocyte subpopulations in patients with syphilis. Issue 1 (February 1982) - Jensen, J R; From, E
Abstract : The distribution of T-lymphocyte subpopulations was studied in 34 patients with primary or secondary syphilis before and after treatment. An absolute and relative T lymphopenia was found in all patients. In primary syphilis the concentration of helper cells--T cells with Fc receptors for IgM (T mu)--was low whereas in secondary syphilis the suppressor cell concentration--T cells with Fc receptors for IgG (T gamma)--was reduced. Using lymphocytes from healthy subjects this could be imitated in vitro by the addition of serum from patients with secondary syphilis. In many autoimmune diseases a low concentration of T gamma may be a primary factor in the production of autoantibodies. The occurrence of similar changes in patients with secondary syphilis, however, indicates that such fluctuations in the T-cell subpopulations may take place during a strong immune response.